Intra-osseous infiltration of adipose mesenchymal stromal cells and plasma rich in growth factors to treat acute full depth cartilage defects in a rabbit model: Serum osteoarthritis biomarkers and macroscopical assessment - Torres-Torrillas, Marta; Damiá, Elena; Peláez, Pau; Miguel-Pastor, Laura; Cuervo, Belén; Cerón, José J.; Carrillo, José M.; Rubio, Mónica; Sopena, Joaquín J. (Frontiers in Veterinary Science, 2022)
Intra-articular infiltration of plasma rich in growth factors (PRGF) and adipose mesenchymal stromal cells (AMSCs) are known to halt osteoarthritis progression, however, in patients severely affected, the treatment cannot reach the deeper layers of the articular cartilage, therefore, its potential is limited. To overcome this limitation intra-osseous infiltrations have been suggested. The purpose of the study is to assess the impact of intra-osseous infiltration of these therapies in serum osteoarthritis biomarkers, and to assess cartilage regeneration macroscopically. A total of 80 rabbits were divided into 4 groups depending on the intra-osseous treatment administered on surgery day: control, PRGF, AMSCs and a combination of PRGF+AMSCs. Additionally, all groups received a single intra-articular administration of PRGF in the same day. Serum biomarkers levels were measured before infiltration and 28-, 56- and 84-days post infiltration. Moreover, a macroscopical assessment was conducted at 56- and 84-days follow-up. Significant lower concentrations of hyaluronic acid and type II collagen cleavage neoepitope were reported in PRGF + AMSCs group at all study times, followed by PRGF, AMSCs and control groups. Regarding macroscopical assessment, lower scores were obtained in PRGF+AMSCs group at all study times. The results suggest that better outcomes are obtain in rabbits with acute chondral defects when intra-articular PRGF is combined with intraosseous PRGF or AMSCs, and that intra-osseous infiltration is a safe procedure.